Pressure Shift Freezing as Potential Alternative for Generation of Decellularized Scaffolds - Eichhorn, S.; Baier, D.; Horst, D.; Schreiber, U.; Lahm, H.; Lange, R.; Krane, M. (International Journal of Biomaterials, 2013)
Background. Protocols using chemical reagents for scaffold decellularization can cause changes in the properties of the matrix, depending on the type of tissue and the chemical reagent. Technologies using physical techniques may be possible alternatives for the production grafts with potential superior matrix characteristics. Material and Methods. We tested four different technologies for scaffold decellularization. Group 1: high hydrostatic pressure (HHP), 1 GPa; Group 2: pressure shift freezing (PSF); Group 3: pulsed electric fields (PEF); Group 4: control group: detergent (SDS). The degree of decellularization was assessed by histological analysis and the measurement of residual DNA. Results. Tissue treated with PSF showed a decellularization with a penetration depth (PD) of 1.5 mm and residual DNA content of 24%±3%. HHD treatment caused a PD of 0.2 mm with a residual DNA content of 28%±.4%. PD in PEF was 0.5 mm, and the residual DNA content was 49%±7%. In the SDS group, PD was found to be 5 mm, and the DNA content was determined at 5%±2%. Conclusion. PSF showed promising results as a possible technique for scaffold decellularization. The penetration depth of PSF has to be optimized, and the mechanical as well as the biological characteristics of decellularized grafts have to be evaluated.